Fábulas como elementos mediadores na construção de conceitos científicos sobre entomologia no ensino médio - Dias, Daniel Pereira do Prado (2021)
One of the main aspects that hinder the learning of entomology concepts in high school refers to the culturally conceived view by society about insects, leading to a lack of knowledge about the biology of these animals. To overcome this conflict, it is important to adopt pedagogical strategies centered on the evolution of everyday concepts, so as to also overcome the fragmentation of knowledge. Therefore, the general objective of this research work was to analyze the contributions of fables, in the light of HistoricalCultural Theory and curricular foundations, for the construction of scientific concepts related to Entomology for the third year of high school. Furthermore, the specific objectives are to identify, in official documents, objects of knowledge linked to entomology in high school and to identify which biological concepts can be built from the use of the fables we produce. The methodology consists of the synthetic documental analysis carried out from the official documents for the third year of high school, in order to gather the skills and objects of knowledge related to entomological studies. The second methodological stage consists of the production of fables through these same concepts and skills listed for the third year of high school. Based on the analyses, we found that both the official documents BNCC and the São Paulo curriculum do not address the issue of insects, as the skills and objects of knowledge are generic and do not explicitly relate to entomology, with the need to seek articulations with entomological knowledge. We also observed that the fables contemplate different biological concepts and that they can serve as a complementary resource for the study of entomology in high school, in order to contribute to the development of Biology classes. Thus, we consider that fables can contribute to the process of forming scientific concepts about insects, in addition to favoring the development of some higher psychological functions.